A case of neonatal jaundice in the newborn child with burdened somatic background - A. A. Afonin; A. A. Lebedenko; T. B. Kozireva; T. D. Tarakanova; M. S. Kasyan; S. E. Avilov; A. A. Vargo; V. K. Korshunova (Медицинский вестник Юга России, 2018)
Jaundice is one of the most frequent metabolic disorders detected in the newborn period. Neonatal jaundice is most likely to be physiological, it is a transient condition and does not require treatment, at the same time it can be a symptom of a serious disease which requires diagnosis and therapy. It is presented a clinical case of conjugational jaundice in newborn from mother with diabetes, with manifestations of hemorrhagic disease. The peculiarity of this case is a complicated course of this disease with hypoxic lesions of the central nervous system and partial intestinal obstruction. In this observation it is shown the effectiveness of the therapy with early diagnosis of the disease and the complications before the appearance of the developed clinical picture.